Adaptive fault-tolerant PI tracking control for ship propulsion system. (September 2018) - Zhao, Zhengen; Yang, Ying; Zhou, Jing; Li, Linlin; Yang, Qingyu
Abstract: This paper studies the fault-tolerant tracking control issues for the ship propulsion system. The propulsion system with one engine and one propeller is first introduced, and the faulty model with loss of actuator effectiveness is formulated. By utilizing the H ∞ output feedback technique, the nominal proportional-integral (PI) controller is designed with its gains analytically determined, yet ensuring the desired tracking performance in the fault-free case. Furthermore, to accommodate loss of actuator effectiveness faults, a fault-tolerant PI control scheme is proposed, including the adaptive tuning law to adjust controller gains online. The proposed strategy is not only simple and easy to implement, but also guarantees the graceful tracking performance and fault-tolerant capability. Finally, a case study on the ship propulsion system is presented to demonstrate the effectiveness of the proposed methods. Highlights: The nominal PI controller is designed with the PI gains analytically determined. An adaptive law is designed to adjust the PI gains to actuator faults with graceful fault-tolerant capability. The proposed adaptive fault-tolerant PI control scheme is verified on the ship propulsion system.